MODELLING OF VEHICLE-KILOMETRES OF TRAVEL BY CAR FOR THE JOURNEY TO WORK IN SYDNEY, AUSTRALIA - Suthanaya, Putu Alit (Jurnal Ilmiah Teknik Sipil; Vol. 10, No. 1 Januari 2006)
In low density, car-dependent cities such as Sydney there have been two drivers of increased VKT: increasing use of the car for the journey-to-work; and increasing spatial separation of homes and workplaces. Descriptive analyses of data from the Census of Population and Housing, Journey-to-Work Tabulations by local government area (LGA), show how person-kilometres of travel by outer suburban residents (greater than 20km for the Sydney CBD) has mushroomed from 1961 to 1996, and how VKT by car has also exploded in the same suburbs (from 1981 when modal data were first reported). The paper describes a modelling framework that allows future VKT by car for the journey to work from LGAs in Sydney to be estimated as a function of future urban form and socio-economic characteristics at the LGA level. Cross sectional and inter-census change statistical models of LGA travel behaviour and urban form (such as, accessibility to employment, density) are fitted. Spatial modelling (the intervening opportunity model) represents the third approach and the LGA preference function (for longer or shorter job destinations) is evaluated across LGAs and through time. A statistical model relates the slope of the preference function (and hence the LGA trip length frequency distribution) to urban form. Nine different scenarios of urban form have been formulated for the year 2011 to test a range of assumptions - existing trends and centralisation / decentralisation of homes and workplaces – and the practical application of the models are demonstrated to evaluate progress towards sustainable transport targets.
Keywords: modelling, VKT, journey to work